2022
DOI: 10.1017/jfm.2021.1147
|View full text |Cite
|
Sign up to set email alerts
|

Onset of wake meandering for a floating offshore wind turbine under side-to-side motion

Abstract: Wind turbine wakes, being convectively unstable, may behave as an amplifier of upstream perturbations and make downstream turbines experience strong inflow fluctuations. In this work, we investigate the effects of the side-to-side motion of a floating offshore wind turbine (FOWT) on wake dynamics using large-eddy simulation and linear stability analysis (LSA). When the inflow turbulence intensity is low, simulation results reveal that the turbine motion with certain Strouhal numbers $St = fD/U_\i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(93 citation statements)
references
References 78 publications
(103 reference statements)
17
76
0
Order By: Relevance
“…They state that the side-to-side motion amplifies the wake meandering when the ambient TI is low (< 3%), leading to a faster recovery of the wake deficit. However, in the TI regime studied here 4 % -8 %, the wake recovery of a floating wind turbine is similar to that of a fixed wind turbine, as reported by (Li et al, 2022). This similarity in wake recovery could explain the agreement of the wake characteristics presented in this analysis with results from previous numerical and wind tunnel studies of fixed wind turbine wakes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They state that the side-to-side motion amplifies the wake meandering when the ambient TI is low (< 3%), leading to a faster recovery of the wake deficit. However, in the TI regime studied here 4 % -8 %, the wake recovery of a floating wind turbine is similar to that of a fixed wind turbine, as reported by (Li et al, 2022). This similarity in wake recovery could explain the agreement of the wake characteristics presented in this analysis with results from previous numerical and wind tunnel studies of fixed wind turbine wakes.…”
Section: Discussionsupporting
confidence: 87%
“…In the case of floating wind turbines, the wind turbine motion that results from the interaction of the floating structure with the wind and sea has to be considered, in addition to the atmospheric conditions. The wake characteristics of floating wind turbines have been studied using numerical (Wise and Bachynski, 2020;Kleine et al, 2021;Nanos et al, 2021;Chen et al, 2022;Li et al, 2022) and wind tunnel (Fu et al, 2019;Schliffke et al, 2020) experiments. Those studies focussed on the impact of the sway (Fu et al, 2019;Nanos et al, 2021;Li et al, 2022), surge (Fu et al, 2019;Schliffke et al, 2020;Chen et al, 2022) and heave (Kleine et al, 2021) motions on the turbine operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of grids is about 13 million. As Li et al [28] selected uniform inflow in his research, an idealized uniform inflow is used in our study to focus only on the effects of yaw control and spacing, and the wake fields under the turbulent inflow with the turbine spacing of 7D are investigated to analyze the influences of the turbulent intensity on the yaw control. The uniform inflow speed is 11.4 m/s.…”
Section: Simulation Settingmentioning
confidence: 99%
“…Moreover, they used their aero‐elastic solver to study half‐wake effects with a one‐way and two‐way wake interactions of two NREL 5‐MW RWT. Recently, Li et al 21 investigated the effects of a floating turbine on the wake dynamics using LES. In line with the findings in the present work, they reported that low turbulence levels were key to the appearance of rotor‐induced wake meandering, which they linked to the side‐to‐side motion of a floating turbine.…”
Section: Introductionmentioning
confidence: 99%